A CASE STUDY ON STUDENT’S SUCCESS IN PERFORMING ENGLISH ORAL FORM AT UMMUL MU’MININ ISLAMIC BOARDING SCHOOL - Rum, Eka Prabawati (Fakultas Keguruan dan Ilmu Pendidikan, 2015)
The study is aimed at investigating some factors contributing to the student’s success in performing English oral form in Ummul Mu’minin Islamic boarding school (UMIBS). It is also aimed at finding out the student’s language learning strategies; the student has to be successful in performing English oral form. The purpose of this research is to describe, explain, and explore issues associated with factors influencing the students’ success in performing English oral form in UMIBS. This research is located within a qualitative research paradigm and was a descriptive and explanatory in nature. In collecting data, the researcher used the following instrument: relevant documents, observation, checklist, questionnaires, and in-depth interview. The researcher observed a sixth-year student, Nur Aisyah Humaira (Mira), who had been successfully performed English oral form in many English competitions. The conclusion of this research are in learning to perform English oral form and learning foreign languages Mira intensively learned by certain preparations that she did almost every day. She used more of her deep level meta-cognitive strategies. Her top priority of English learning orientation, in general, was to travel abroad and to keep in touch with friends of her who were living in other countries where the main language was spoken was English.